Protilátky proti arbovirům u lovné zvĕre odchycené na Moravĕ - Juricová, Z (Veterinarni medicina, 1992)
The HIT method was used to examine blood serums of the game in Moravia (roebuck, red deer, fallow deer, mouflon, wild boar, brown hare) for the presence of antibodies to arboviruses of these groups: alphavirus (Sindbis-SIN), flavivirus (West Nile-WN), tick-borne encephalitis (TBE) and Bunyamwera (Tahyna-TAH, Calovo-CVO). Antibodies to all viruses were detected, and namely in these frequencies: SIN 0.9%, WN 16.9%, TAH 41.5%, CVO 23.1% and TBE 8.5%.
Keywords: arboviry; Animals, Wild; Czechoslovakia; protilátky virové; zvířata; divoká zvířata; Mammals; savci; Československo; Animals; Antibodies, Viral; Arboviruses